Protecting the Rights of E-consumers through Judicial Process in Nigeria: An Appraisal - Nuruddeen, Muhammad; Yusof, Yuhanif; Abdullah, Nor Anita (2017)
Electronic commerce (e-commerce) is the buying, selling as well as advertisement of goods and services on the Internet.Thus, the Internet has now given birth to yet another group of consumers known as electronic consumers (e-consumers).The e-consumers are increasing in number over the years as online commercial transactions become a new way of lifestyle across the globe. Consequently, the United Nations and other international organisations made a call for the establishment of consumer institutions to ensure adequate protection of the e-consumers.This is necessary given the susceptibility of the e-consumers to deceptive and unfair trade practices. Therefore, the objective of this paper is to examine the role of the Nigerian courts in protecting the legitimate interest of the e-consumers. The paper adopts doctrinal and empirical methodologies to achieve its tasks. The paper discovers that the judicial system of protecting the rights of consumers and e-consumer in Nigeria is costly, time-consuming and full of procedural technicalities.The paper also reveals that courts in Nigeria are overburden.Besides, the majority of the Judges handling econsumer disputes lack requisite expertise and knowledge about e-commerce and Information Communications Technology (ICT) matters.To address problems associated with delay, the cost of ligation and technicalities in judicial proceedings, this paper, therefore, recommends the establishment of Small Claims Courts in Nigeria. The paper also recommends regular training for the Nigerian Judges in the areas of e-commerce and consumer related issues.